ChemInform Abstract: A Convenient Palladium‐Catalyzed Carbonylative Synthesis of 2‐Aminobenzoxazinones from 2‐Bromoanilines and Isocyanates. Issue 40 (12th September 2013) - Wu, Xiao‐Feng; Sharif, Muhammad; Shoaib, Khurram; Neumann, Helfried; Pews‐Davtyan, Anahit; Langer, Peter; Beller, Matthias
Abstract Compared with previously described methods for the synthesis of 2‐aminobenzoxazinones, Mo(CO)6 is applied as a solid CO source instead of gas in this procedure.